The Role of General Criminal Investigation in Tackling Human Trafficking - Sitti Fatimah Maddusila (Program Pascasarjana Universitas Muhammadiyah Palu, 2025)
This study aims to: (1) To find out the efforts made by the General Criminal Investigation Unit of the Central Sulawesi Regional Police in tackling the crime of trafficking in persons (2) To find out the obstacles faced by the General Criminal Investigation Unit of the Central Sulawesi Regional Police in tackling the crime of trafficking in persons. The method used in writing this is to use an empirical juridical research approach. The results of this research are (1) The Police as law enforcers, protectors and protectors of the community are obliged to maintain the uphold of the law, justice and protection of human dignity as well as order and legal certainty in order to realize the duties and functions of the police, there are several efforts made by the Central Sulawesi Police, especially the criminal investigation unit in overcoming the prevention of human trafficking crimes, namely through the efforts of the Central Sulawesi Police. Pre-emptive, through preventive efforts and through repressive efforts. (2) The prevention of trafficking in persons carried out by the General Criminal Investigation of the Central Sulawesi Regional Police has several obstacles, including victims of trafficking in persons who do not want to report, and the lack of budget for the prevention of trafficking crimes, when this is an obstacle to the general criminal investigation of the Central Sulawesi Regional Police in preventing the crime of trafficking in persons. The Research Suggestions are (1) There is a need for special attention and support from various institutions and the community is also needed to handle trafficking cases. Information and news from trafficking cases need to be reported more to increase public attention so that cases about Human Trafficking do not occur again (2) The government should form a special task force to tackle the crime of trafficking in persons consisting of the police, the Ministry of Manpower and the Protection of Indonesian Workers.